New Shunosaurus (Dinosauria: Sauropoda) material from the middle Jurassic lower Shaximiao Formation of Yunyang, Chongqing, China. (3rd June 2022) - Ma, Qingyu; Dai, Hui; Tan, Chao; Li, Ning; Wang, Ping; Ren, Xinxin; Meng, Li; Zhao, Qi; Wei, Guangbiao; Xu, Xing
ABSTRACT: Shunosaurus is a small eusauropod from China. It is characterised by solid cervical and dorsal vertebral centra without complicated pneumatic structures, platycoelous or amphicoelous middle and posterior vertebrae and a lack of pubic foramen in adult individuals. Although many Shunosaurus individuals have been discovered, the ontogenetic characteristics of its long bones and bone tissues are not very clear and the existing description of the postcranial skeleton is relatively rudimentary. The new well-preserved and the smallest Shunosaurus specimen discovered in Yunyang, Chongqing, China, provides good material for solving these problems. The radial distal breadth is more than twice the minimum midshaft breadth, and the fibular distal end is twice as wide as the midshaft, while these ratios are all smaller in adult specimens. The lateral trochanter is undeveloped. This individual does show a pubic foramen. The degree of vascularisation of the bone tissue in the juvenile bone tissue is higher for adults. There are no arrested growth lines and peripheral rest lines in the compact bone, indicating that body size still increases slowly after maturity. The discovery of this new material expands the distribution range of Shunosaurus in China.